Leachate permeability of compacted soil barrier / Ahmad Fadzil Mohd Rose - Mohd Rose, Ahmad Fadzil (1997)
Landfill represents the permanent or semi permanent burial of solid, liquid and or semisolid. The migration of both original waste components or decomposed by product such as leachate or gaseous emission must be contained within the landfill or manageabie abstracted and destabitised. The primary parameter that influences the contaminant of waste is the permeabüity of the 'engineered soil barrier(soil)'. This study , therefore investigate the parameter that effect leachate permeabüity of engineered soil barrier. The compacted soü banier examines in this laboratory investigation are : süt of high plasticity (MH) and clay of low plasticity (CL).The sous were compacted at different energy level, and different moisture content. A falling head permeameter were used to measure both water and leachate permeabüity of the soil. The following conclusions can be made leachate permeabüity, kc for compacted cohesive soü; • noticed from the experimental studies , the maximum permeabüity occurs of the optimum water content, and • permeabüity is largeiy depends on the concentration of ieaching solution.